A theranostic Mn-based metal-organic framework for T1-weighted magnetic resonance property and chemodynamic therapy. (1st September 2021) - Yu, Shijiang; Lin, Wenxin; Huang, Xiajuan; Jin, Xiaokang; Yao, Shuting; Wang, Bing; Zhu, Hongliang; Chen, Jianjun
Graphical abstract: The Mn-DA exhibited magnetic resonance property and the ability of free radical generation to kill cancer cells. To further improve the theranostic properties, Mn 2+ was selected and loaded into Mn-DA to obtain Mn@Mn-DA. It showed better theranostic effect in vitro, providing a simple method to build effective systems for anti-cancer. Abstract: A Mn-based metal-organic framework Mn-DA was synthesized from MnCl2 and organic azo ligand H4 DA, and it was characterized by single crystal X-ray diffraction analysis, PXRD, FT-IR and TGA. The materials containing Mn 2+ displayed magnetic resonance property and the ability of chemodynamic therapy. Then Mn 2+ was selected and loaded into Mn-DA, which was called Mn@Mn-DA, to further improve the theranostic properties. Comparing with Mn-DA, Mn@Mn-DA exhibited more than twice of the relaxation rate and better chemodynamic therapy effect. Mn-based metal-organic framework Mn-DA showed ideal T1-weighted magnetic resonance property and chemodynamic therapy. In addition, the successful fabrication of Mn@Mn-DA provided a simple strategy to construct more effective systems for theranostic application.